Geotechnical and geophysical site characterization 4 : proceedings of the fourth International Conference on Site Characterization, ISC-4, Porto de Galinhas, Pernambuco, Brasil, 17-21 September 2012 /: proceedings of the fourth International Conference on Site Characterization, ISC-4, Porto de Galinhas, Pernambuco, Brasil, 17-21 September 2012. (©2013) - Unknown
No abstract available